Optimization of Tourism Potential in An Effort to Empower Tourism-Conscious Communities - Danang Wikan Carito; Moh. Hudi Setiyobakti; Riza Bahtiar Sulistyan; Fauzan Muttaqien (TGO Journal of Community Development, 2023)
The external targets in this Community Partnership Program include increasing public awareness in tourist attractions to always maintain the cleanliness of the environment of natural bathing attractions of Sumber Mrutu starting from the entrance to tourist attractions, the beauty of tourist attractions that later tourists or visitors can enjoy the atmosphere of the natural bathing tourist attractions of Sumber Mrutu, jiwa the community serves to visit becomes its own value to tourists who come to the natural tourist attractions of Sumber Mrutu, theincrease in the economic value of the community and Pandansari Village government, creatingwebsites and other social media as a means of promoting the natural baths of Sumber Mrutu. The Community Partnership Program Plan proposed by the proposing team is the socialization of Tourism Awareness and strengthening of Human Resources to the pandansari village community, a training method through Marketing Management and Human Resource Management practices, evaluation methods by conducting pre-tests and post-tests, making the official website of natural bathing tourism Sumber Mrutu Pandansari village up to the management of the Website.